![{x}^{3} - {y}^{3} = (x - y)( {x}^{2} + xy + {y}^{2} ) {x}^{3} - {y}^{3} = (x - y)( {x}^{2} + xy + {y}^{2} )](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D+-++%7By%7D%5E%7B3%7D+%3D+%28x+-+y%29%28+%7Bx%7D%5E%7B2%7D++%2B+xy+%2B++%7By%7D%5E%7B2%7D+%29)
Answers
Answered by
9
We know that
First take R.H.S
=> x3 - x2y + xy2 + x2y - xy2 + y3
{On multiplying x3 + y3 with (x+y) ( x2 - xy + y2)}
=> [x3 + y3] + ( -x2y + x2y) + ( xy2 - xy2)
=> x3 + y3
Since R.H.S = L.H.S,
That is x3 + y3 = x3 + y3
Hence, verified that
x3 + y3 = (x+y) ( x2 - xy + y2)
✄✄✄plsss mark my answer as brainliest
hope its helpful
Answered by
1
Answer:
Step-by-step explanation:
mil gayi yahhhhhhhh
followers badhane hai kya ?
Similar questions